1987
DOI: 10.1007/bf00581337
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of calcium-activated potassium channels in single smooth muscle cells using the patch-clamp technique

Abstract: Single-channel currents were recorded with the patch-clamp technique from freshly dissociated vertebrate smooth muscle cells from the stomach of Bufo marinus. Of the variety of channels observed, one displayed a large linear conductance of 250 pS (in symmetric 130 mM KCl) which in excised patches was shown to be highly K+ selective. The probability of the channel being open (Po) increased when [Ca2+]i was elevated and/or when the membrane potential was made more positive. Thus, the features of this channel res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
90
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(106 citation statements)
references
References 53 publications
15
90
1
Order By: Relevance
“…shortening of the closed state and partially to prolong the open state. The effect of depolarization was found to be the same as that of increasing [Ca]; in the toad stomach cells [53].…”
Section: Ca-activated K Channelsmentioning
confidence: 68%
See 2 more Smart Citations
“…shortening of the closed state and partially to prolong the open state. The effect of depolarization was found to be the same as that of increasing [Ca]; in the toad stomach cells [53].…”
Section: Ca-activated K Channelsmentioning
confidence: 68%
“…The presence of K channels controlled by intracellular Ca (Ca-activated K channels) has been demonstrated in several smooth muscles by recording currents flowing through a single channel with the patch-clamp method (toad and frog stomach [10,52,53,63]; rabbit portal vein [28,29]; rabbit jejunum and guinea-pig mesenteric artery [7,8]; canine trachea [37]). From the effect of altering ionic composition of the media, it has been shown that these channels are highly selective to K ions, activated by a low concentration of cytoplasmic Ca (0.01-1 µM), and have a very high conductance (200-270 pS at a symmetrical high K concentration).…”
Section: Ca-activated K Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, over the range of patch membrane potentials that occurred during our experiments, the fraction of the SAC current that is carried by Ca 2ϩ appears to be relatively independent of this parameter. Ca 2ϩ entering the cell through SACs is sufficient to cause a substantial local increase in the free [Ca 2ϩ ] (see discussion), as indicated by large-conductance Ca 2ϩ -activated K ϩ (BK Ca ) channel (19) openings in the same patch (Fig. 5).…”
Section: A Localized Fluorescence Transient Caused By Ca 2؉ Entry Thrmentioning
confidence: 97%
“…Over the range of potentials used here, the voltage dependence of activation can be described by a Boltzmann relationship such that a plot of ln NP o as a function of membrane potential is linear at low values of P o . The reciprocal of the slope ("slope factor"), a measure of the voltage dependence of channel gating, is the potential required to produce an e-fold change in P o (Singer and Walsh, 1987). Data from an inside-out patch (Fig.…”
Section: Channel Activation By Bile Acids Is Not Due To Changes In Thmentioning
confidence: 99%